EFL TEACHERS’ STRATEGIES FOR TEACHING WRITING IN DIGITAL LEARNING ENVIRONMENTS - Siswana; Sriyanto, Widi; Komara, Cahya (ELLTER Journal, 2025)
This study investigates the strategies employed by English as a Foreign Language (EFL) teachers in teaching writing through digital learning environments, with a specific focus on the use of Google Docs as an instructional tool. Adopting a qualitative descriptive approach, the research involved ten EFL teachers from various educational levels in the Greater Jakarta area. Data were collected through non-participant classroom observations and semi-structured interviews. The findings reveal that Google Docs plays a central role in supporting collaborative drafting, structured feedback, real-time revision, and student autonomy. Teachers utilized Google Docs to facilitate both synchronous and asynchronous writing instruction, integrating it with platforms such as Google Classroom and WhatsApp to build a cohesive digital learning ecosystem. Overall, the integration of Google Docs was perceived as effective in enhancing student engagement, improving writing quality, and streamlining the feedback process. The study concludes that digital platforms, when purposefully implemented, can significantly enrich EFL writing pedagogy in contemporary classrooms.